Contemporary therapeutic options for children with high risk neuroblastoma - Sterba, J (Neoplasma, 2002)
Despite the use of aggressive chemotherapy, stage 4 high risk neuroblastoma still has a very poor prognosis, which is estimated at 25%. Therefore, novel treatment approaches are needed. Increasing number of reports has been concerned with the use of novel treatment modalities. Literature regarding intensive induction, local therapy, myeloablative therapy and immunotherapy and biotherapy was reviewed in order to draw conclusions and recommendations for the management of children with high risk neuroblastic tumors.
Keywords: transplantace kostní dřeně; Bone Marrow Transplantation; Child; isotretinoin; Neuroblastoma; Gangliosides; dítě; monoklonální protilátky; Antibodies, Monoclonal; gangliosidy; čištění kostní dřeně; lidé; neuroblastom; Humans; Bone Marrow Purging; Isotretinoin